Moral Distress in Family Health Strategy: experiences expressed by daily life - Cecília Maria Lima Cardoso; Maria Odete Pereira; Danielle de Araújo Moreira; Hanna Beatriz Bacelar Tibães; Flávia Regina Souza Ramos; Maria José Menezes Brito (SciELO, 2016)
Objective Understanding the Moral Suffering experiences expressed in the daily life of the Family Health Strategy. Method This is a case study with a qualitative approach, conducted between August and October 2014 in a municipality of Minas Gerais. The sample was represented by 28 professionals of family health teams. Data were collected through interviews with semi-structured questionnaires, observation, projective technique and submitted to thematic content analysis. Results The results indicate that routine issues of the health care system lead professionals to experience a challenging practice in dealing with daily situations that contradict their ethical precepts and can compromise the quality of work, becoming triggers of Moral Distress. Conclusions Social vulnerabilities such as domestic violence, poor socioeconomic conditions and organizational weaknesses of the health system were the main triggers of Moral Distress. Therefore, it is necessary to amplify this reflection by workers of the Family Health Strategy, aiming to encourage the minimization of suffering experiences, considering their ethical values.